ӨЗБЕК АЛЫМЛАРЫ ҒӘРЕЗСИЗЛИКТЕН КЕЙИНГИ ДӘЎИРДЕ ЖОҚАРҒЫ ҚАРАҚАЛПАҚЛАР ҲАҚҚЫНДА - Прекеева, Амангүл; Қутлымуратов, Илхамжан (FAN va JAMIYAT, 2026)
This article is devoted to the information published in the scientific literature by Uzbek scientists about the upper Karakalpaks in the post-independence period.